COMMUNITY STRUCTURE AND REGENERATION STATUS OF TREE SPECIES IN KYONGNOSLA ALPINE SANCTUARY, EASTERN HIMALAYA, INDIA - Subhajit Lahiri; Sudhansu Sekhar Dash (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2021)
Habitat destruction, over exploitation, monoculture are major reasons for loss of primary forests in Himalaya. Tree population, composition and diversity particularly in the temperate Himalaya play a key role in the maintenance of many ecosystem services and natural biogeochemical cycles. The present study explores composition and regeneration status of tree species in a temperate mixed forest in Kyongnosla Alpine Sanctuary, East Sikkim, India. Two sites at an elevation range of 2800–3800 m were selected and 20 plots of 20 m × 20 m for trees, 80 plots of 5 m × 5 m for saplings, and 160 plots of 1 m × 1 m for seedlings were sampled to study the regeneration status. A total of 17 tree species belonging to 9 genera and 8 families were recorded of which Rhododendron was the most dominant genus with maximum number of species. All the phytosociological attributes, such as relative density, abundance and important value index were calculated. The average species richness of adult trees and saplings was 13.5± 0.7 and for seedlings it was 12.5 ± 0.07. The mean density of seedlings was 3609.77 ± 494.39 individuals/ ha, for saplings 1540 ± 113.13 individuals/ha and of mature trees 548.75 ± 8.83 individuals/ha. Total basal area cover ranged from 36.61 to 40.35 m2/ha for trees, from 1.54 to 1.71 m2/ha for saplings. Fair regeneration was observed in 64.72% of total species; good regeneration observed in 17.64% species, 11.76 % species exhibited poor regeneration while 5.88% showed no regeneration. Density-diameter distribution exhibited decrease in tree densities towards higher DBH classes. The study not only provides reliable information on the ecosystem’s health of the sanctuary but also will help in understanding the complexity of the ecosystem function and an approach to conservation of biota.